Educação emocional na educação infantil: concepções da docência sobre as competências socioemocionais da BNCC - Dalagnol, Rosângela Fátima (2020)
The present article which is entitled “Emotional Education: teaching conceptions about socio-emotional competences of BNCC's” has as theme “The development of socio-emotional in the first childhood” and aims to identify the perceptions of pedagogical coordinators and teachers of Primary Education municipal schools in the municipality of Erechim/RS about socio-emotional educations and the socio-emotional competences for Early Childhood Education present in the National Common Curricular Base (BNCC). The referred research is of applied nature, with a qualitative approach and of a descriptive-interpretative character and was carried out through bibliographic study and field research. Data collection, held in four of the eight early childhood schools in the municipality of Erechim/RS, from which two are located in peripheral neighborhoods and other two are located in the city center, happened by the means of structured audio-recorded interviews with three teachers, and a pedagogical coordinator from each school, adding up to twelve teachers and four pedagogical coordinators, totalizing sixteen interviewed people. Later, the transcription of the speeches, categorization and content analysis were carried out, followed by the interpretation of the data, based on theoretical concepts relevant to the theme, presented by authors such as Goleman (1995), Gerhardt (2017), Damásio (2000), Wallon (1989), Piaget (2010) e Vygotsky (2010). By highlighting the conception of a child, it was noticed that there is no consensus among teachers due to the use of several adjectives. Regarding the presence of emotions in Early Childhood Education, it was found that they present themselves in an intense, constant and spontaneous way at all times and spaces, directly influencing daily life. When considering the teachers' perception of emotional education and the development of socio-emotional skills proposed at BNCC, it was identified that these are considered, by teachers, as indispensable for the integral training of subjects. However, the necessity of deepening the knowledge regarding the theme and its importance was noticed. Also, it could be evidenced that the training carried out for the implementation of the BNCC was not enough for the teachers to feel safe when contemplating the practice in a manner which is aligned with the proposals presented in the document. Thus, the necessity of approximation between school, family and community was identified, with the objective of searching partnership, cooperation and responsibility from everyone for the socio-emotional and integral development of children. Equally, it was shown that the strategies used by teachers for socio-emotional development are supported by a behavioral bias and by the use of rules and agreements. However, it is emphasized that socio-emotional education must permeate all moments and spaces, having its effectiveness through interactions and games. It has been 11 revealed that teachers need to talk about their emotions and distresses, evidencing that they need to be taken care of so they could take care and educate of the children. It should be noted that the results point to the urgency of reviewing and re-editing the curriculum for initial formation and continued training, not forgetting about self-training as an ally in the processes of constant formation, indispensable requirement to the teaching profession.